Answer:
![a_9=48](https://tex.z-dn.net/?f=a_9%3D48)
Step-by-step explanation:
we are given
sequence is geometric
so, we can use nth term formula
![a_n=a_1(r)^{n-1}](https://tex.z-dn.net/?f=a_n%3Da_1%28r%29%5E%7Bn-1%7D)
we have
![a_1=3](https://tex.z-dn.net/?f=a_1%3D3)
![r=\sqrt{2}](https://tex.z-dn.net/?f=r%3D%5Csqrt%7B2%7D)
we have to find a9
so, we can plug n=9
we get
![a_9=3(\sqrt{2})^{9-1}](https://tex.z-dn.net/?f=a_9%3D3%28%5Csqrt%7B2%7D%29%5E%7B9-1%7D)
![a_9=2^4\cdot \:3](https://tex.z-dn.net/?f=a_9%3D2%5E4%5Ccdot%20%5C%3A3)
![a_9=48](https://tex.z-dn.net/?f=a_9%3D48)
I’m not sure sorrry but i hope someone else can help u
Answer:
x=3, z=-1, y=6
Step-by-step explanation:
you need to make the coefficients of each variable equal to each other then subtract 2 equations.
this one: multiply -4 in 1st
4x+4y+4z=32
-4x+4y+5z=7
_____________
8x+0-z=25
we have 2 equations with 2 variables now
2x+2z=4
8x-z=25
Answer:
B. 1/9
Step-by-step explanation:
The positive square root of "x^2 - 4x + 4" is "x - 2". That value is already given to you, 1/3. Just square 1/3 to get 1/9.
I think you should go with A).